PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 28 PADANG TAHUN PELAJARAN 2013/2014 - Musneri, Mairinda; Rismen, Sefna; Pratiwi, Merina (STKIP PGRI Sumbar, 2013)
This research was conducted based on the phenonema indicating Â that the students have no concern with learning that their understanding of mathematical concept have low, that can be seen from the completion percentage of II-semester examination points of VII- and VIII-grade students. The purposes of this research are to know the student activities by applying the guided-note-taking-type active learning strategy and the student understanding of mathematical concept by usingÂ the active learning strategy with Guided Note Taking type was better than the student mathematical concept apprehension by applying the conventional learning of the VIII-grade students of SMPN 28 Padang. This was experimental research. The instruments used in this research are observation sheet of student activities and final tests. Â The results of student activity analysis show that the activities risen Â an improvement, and from the hypothesis testing it is obtained that P-value is 0.009 so that H0 is rejected and the hypothesis is accepted. It can be concluded that the student activities can improve by applying the guided-note-taking-type active learning strategy and the studentsâ understanding of mathematical concept by using this strategy was better than that by using the conventional at the VIII-grade of SMPN 28 Padang.